Somalia: The Challenges of Rebuilding Public Services in a Collapsed State - Fidow, Ahmed Mohamed Hassan; Ahmed, Hibo Ilyas (School of Social Sciences, USM, 2017)
Public service of each country stands out the foremost instrument of government formulation and implementation of public policies. It transforms government programs into concrete goods and services for the use and benefit of the citizens. Public services are vital in human life and are the obligation of each government on the world to provide services in order to protect the wellbeing of its people. Once a state collapses, the fragmentation of the structure, authority, law and order inside the state occurs. Collapsed states are referred to those which can’t perform the functions anticipated of a state. But, after the collapse of the Somalia’s central government, the country has faced many problems such as social, political, economic, environmental and technological. More than twenty years of civil war, lack of government, violence, poverty, drought cause society more vulnerable to everything. Since the beginning of 2000 until now, Somalia has had its own government, but it failed to restore the delivery of public services. On the other hand, these services remained in the hands of private sector. This paper aims to explain the challenges of rebuilding public services in Somalia and how to restore these public services in a collapsed state.